One day on Earth [videorecording (DVD)] - Ruddick, Kyle (Docurama Films ; Distributed by New Video, 2013)
On 10-10-10, across the world, documentary filmmakers, students and other inspired citizens recorded the human experience over a 24-hour period and contributed their voices to a global day of media creation called One day on Earth. Over 3,000 hours of footage were filmed. It was the first ever simultaneous filming event occurring in every country in the world. Depicts the diversity, conflict, tragedy, and triumph that occur in one day.